The Effect of Performance Allowances on the Discipline and Performance of Civil Servants at The Class II Immigration Office (TPI) of Bagansiapiapi - Rotua Hotmasari Hasibuan; Sri Sediyaningsih; Meyzi Heriyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the effect of performance allowances on work discipline and performance among civil servants at the Bagansiapiapi Class II Immigration Office (TPI) and examine the role of work discipline as a mediating variable in this relationship. The research method used was a quantitative approach with an explanatory research approach. The study population consisted of 35 employees, all of whom were sampled using a census technique. Data were collected through a Likert-scale questionnaire and analyzed using path analysis. The results showed that performance allowances had a positive and significant effect on employee work discipline. However, performance allowances did not directly affect employee performance. Work discipline was shown to have a positive and significant effect on employee performance and was able to mediate the effect of performance allowances on employee performance. These findings indicate that improved employee performance is determined not only by the provision of performance allowances but also by the level of employee work discipline. The conclusion of this study is that performance allowances are more effective in improving employee performance through improved work discipline. Therefore, the implementation of performance allowance policies needs to be integrated with a consistent discipline monitoring and performance evaluation system to achieve optimal employee performance. Keywords: Performance Allowances, Work Discipline, Employee Performance, Civil Servants